Kenya print media performance and the social construction of identity: Raila Odinga in the Nation and The Standard newspapers (1997-2017) - Ochoti, Fred Orina (Stellenbosch : Stellenbosch University, 2024)
Thesis (DPhil)--Stellenbosch University, 2024.